Growth of winter wheat adapting to climate warming may face more low‐temperature damage. (13th December 2022) - Song, Yanling; Zhou, Guangsheng; Linderholm, Hans W.; Wang, Junfang; Li, Yong; Wang, Guofu; Fu, Yan; Xu, Jinxia; Shi, Ying; Xu, Ying; Gao, Hui; Chen, Deliang
Abstract: China's surface air temperature is increasing due to global warming, so it is interesting that how low temperatures would be changed during the growth period of winter wheat in future. We focused on the low temperatures of winter wheat from 2021 to 2050, using temperatures under the high emission scenario Representative Concentration Pathway 8.5 (RCP8.5) projected by the RegCM4.4 regional climate model. The results showed that the annual mean temperature was projected to increase by 0.42°C⋅decade −1 in the northern and by 0.35°C⋅decade −1 in the southern winter wheat region. Furthermore, the temperature was expected to increase rapidly in spring, which could advance the dates of flowering and the start of the grain‐filling period. Using the genetic parameters determined by the calibration and validation of WOFOST and bias‐corrected projected meteorological data, simulations of winter wheat growth were performed over the winter wheat region for 2021–2050. The simulated number of days to the flowering period of winter wheat for 2041–2050 was on average 6.5 days less than in 2021–2030, due to the spring warming. Because of the earlier start of the growing season, winter wheat could face negative effects by being subjected to low temperatures. Indeed, the number of low‐temperature days was projected to increase by 110% from 2041 to 2050 compared to 2021–2030, and the number of killing degree days (KDDs) is projected to increase by 120% at the same time. If the number of days to flowering did not change, the number of low‐temperature days and KDDs only changed slightly, showing that the negative influence of low temperature was mainly caused by the advancement of the flowering date. The effect of low temperature on growth was underestimated when the response of winter wheat growth to global warming was not considered. Abstract : The number of low‐temperature days is indeed projected to increase by 110% from 2041 to 2050 compared with the period of 2021–2030, and the number of KDDs is projected to increase by 120%. The effect of low temperature on growth was underestimated when the response of winter wheat growth to global warming was not considered. Number of low‐temperature days and KDD with changes in the flowering and maturity date simulated by the WOFOST model were compared to the situation with no changes in flowering and maturity from 2021 to 2050 under the RCP8.5 scenario.